Knowledge and attitudes of medical students in Lebanon toward artificial intelligence: A national survey study - Doumat, George; Daher, Darine; Ghanem, Nadim-Nicolas; Khater, Beatrice (Frontiers in Artificial Intelligence, 2022)
Purpose: This study assesses the knowledge and attitudes of medical students in Lebanon towards Artificial Intelligence (AI) in medical education. Methods: This is a cross-sectional study using an online survey consisting of close-ended questions. The survey targets medical students at all medical levels across the 7 medical schools in Lebanon. Results: A total of 206 medical students responded. The majority (81.1%) got their information about AI from the media. Students in their clinical years appear to be more knowledgeable about AI in medicine. Around a quarter of students (26.8%) reported that advancements in AI affected their choice of specialty. Students who learned the basics of AI as part of the medical school curriculum were more knowledge about AI than their peers who did not. Finally, only a quarter of students (26.5%) want to be assessed by AI, even though the majority (57.7%) reported that assessment by AI is more objective. Conclusions: Education about AI should be incorporated in the medical school curriculum to improve the knowledge and attitudes of medical students.